2018
DOI: 10.1039/c8ra01882k
|View full text |Cite
|
Sign up to set email alerts
|

Roles of membrane protein damage and intracellular protein damage in death of bacteria induced by atmospheric-pressure air discharge plasmas

Abstract: Although plasma sterilization has attracted much attention, the underlying mechanisms and biochemical pathways are still not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…This is supported by a work of Hao Zhang et al It is found that α‐helix content decreases and β‐sheet increases in both membrane and intracellular proteins with regard to after‐charge storage. [ 30 ] Moreover, the amide I/II intensity ratio is a good indicator of protein secondary structures. [ 48 ] In this study, this ratio increased monotonically with treatment time (1.49, 1.52, 1.56, and 1.63 for 0, 60, 90, and 120 s of exposure time, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a work of Hao Zhang et al It is found that α‐helix content decreases and β‐sheet increases in both membrane and intracellular proteins with regard to after‐charge storage. [ 30 ] Moreover, the amide I/II intensity ratio is a good indicator of protein secondary structures. [ 48 ] In this study, this ratio increased monotonically with treatment time (1.49, 1.52, 1.56, and 1.63 for 0, 60, 90, and 120 s of exposure time, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] In other research studies, various biological effects of plasma on bacteria are investigated. In summary, membrane integrity loss, [ 25,28 ] lipid peroxidation, [ 25,28,29 ] protein oxidative modifications, [ 16 ] changes in protein secondary or/and tertiary structures, [ 30 ] oxidative DNA damages, [ 28,31 ] and protein–DNA crosslink [ 32 ] are observed in treated bacterial solutions. Nevertheless, more efforts are required to clarify the effects of plasma on macromolecules in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-irradiated solutions with anticancer effects are termed plasma-activated solutions [ 33 ]. It is considered that, during CAP irradiation, the solutions were enriched with a wide variety of aqueous ROS and RNS, such as hydrogen peroxide (H 2 O 2 ), hydroxide radicals (OH•), superoxide anion radicals (O 2 − ), ozone (O 3 ), nitrite ions (NO 2 − ), peroxynitrite (ONOOH/ONOO − ), and nitrate ions (NO 3 − ) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. These aqueous ROS and RNS can trigger intracellular oxidative stress, mitochondrial dysfunction and DNA damage, and further activate the related signaling pathways of programmed cell death [ 23 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–16 ] When cells are treated with CAP, these gas‐phase reactive species react with aqueous solutions to produce a rich variety of liquid‐phase reactive species, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS). [ 17–21 ] These liquid‐phase reactive species can act on cells and induce an increase in intracellular ROS levels. [ 3,20,22–24 ] Cells also accumulate ROS and other byproducts during normal oxidative respiration and metabolism.…”
Section: Introductionmentioning
confidence: 99%